1977
DOI: 10.1111/j.1399-3054.1977.tb09281.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of 1,2‐14C‐(Chloroethyl) Phosphonic Acid (Ethephon) in Olive (Olea europea)

Abstract: The translocation and metabolism of ethephon at pH 7.0 and its effect on abscission of olive fruit, were studied in attached and detached fruits. In detached olives, the lowest fruit removal force values were achieved when the fruits were treated at their proximal cavity and kept under humid conditions. Following application of 14C‐ethephon to the proximal cavity 63% of the label was absorbed within 4 h; evolution of 14C‐ethylene proceeded at a slow rate, mainly from 14C‐ethephon remaining on the olive surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…3 and 4), and a large proportion may enter the leaf just before complete evaporation of the liquid when the ethephon exists in a highly concentrated solution. This pattern of rapid ethephon uptake into olive fruits was noted by Epstein et al (1977) and similar conclusions were reached for gibberellic acid in citrus tissues (Greenberg and Goldschmidt 1990). Variability between individual leaf disks was high where some replicates had dried droplets and some remained wet (e.g., some large error bars in Figs.…”
Section: Treatmentsupporting
confidence: 52%
“…3 and 4), and a large proportion may enter the leaf just before complete evaporation of the liquid when the ethephon exists in a highly concentrated solution. This pattern of rapid ethephon uptake into olive fruits was noted by Epstein et al (1977) and similar conclusions were reached for gibberellic acid in citrus tissues (Greenberg and Goldschmidt 1990). Variability between individual leaf disks was high where some replicates had dried droplets and some remained wet (e.g., some large error bars in Figs.…”
Section: Treatmentsupporting
confidence: 52%
“…Researchers have reported that raising pH from 3 to ≈7 decreased FRF, presumably because of the more rapid release of ethylene from ethephon at that pH (Ben-Tal and Lavee, 1976aLavee, , 1976b. A body of literature has evolved based on this point, and the presumed pulse of ethylene that comes from ethephon decomposition as the daily temperature rises in the field increases the decomposition rate (Epstein et al, 1977;Klein et al, 1978Klein et al, , 1981. In most cases in which ethephon was used, the pH was raised using phosphate buffers.…”
Section: Resultsmentioning
confidence: 99%
“…Penetration of ERCs into plants and their subsequent movement within plant tissues can influence their effectiveness (Kays and Beaudry, 1987). Epstein et al (1977) studied penetration of 14 C-ethephon at pH 7 in phosphate buffer into attached and detached olives and rachides (pedicels). More radiolabeled material was found in the fruit when 14 C-ethephon was applied at the distal end of the fruit than when it was applied to the pedicel-fruit cavity.…”
mentioning
confidence: 99%
“…Some investigators claimed that ethephon is not translocated at all [10,12,13] ; others demonstrated good and rapid translocation of 14 C-ethephon [21,23,24] . Still others reported that translocation occurs in some tissues but not in others [13,20], or that the moving compounds are actually labelled products of the 14 C-ethephon applied [9,13,14] .…”
Section: Discussionmentioning
confidence: 99%